2020
DOI: 10.1212/wnl.0000000000010010
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing 2,589 child neurology telehealth encounters necessitated by the COVID-19 pandemic

Abstract: Objective:To assess the rapid implementation of child neurology telehealth outpatient care with the onset of the COVID-19 pandemic in March 2020.Methods:This was a cohort study with retrospective comparison of 14,780 in-person encounters and 2,589 telehealth encounters including 2,093 audio-video telemedicine and 496 scheduled telephone encounters between 10/1/19 and 4/24/2020. We compared in-person and telehealth encounters for patient demographics and diagnoses. For audio-video telemedicine encounters, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
157
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(176 citation statements)
references
References 14 publications
15
157
2
2
Order By: Relevance
“…(2020) USA Descriptive Allergy & Immunology Apr. 13-May 8, 2020 177 out of 290 who received telemedicine completed satisfaction survey; 65% females Median age – 33 years old; 65% females; 41% were new patient (NP) encounters Rochester, NY Survey LOE VI Rametta et al. (2020) USA QI Pediatric Oct. 1 to Mar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) USA Descriptive Allergy & Immunology Apr. 13-May 8, 2020 177 out of 290 who received telemedicine completed satisfaction survey; 65% females Median age – 33 years old; 65% females; 41% were new patient (NP) encounters Rochester, NY Survey LOE VI Rametta et al. (2020) USA QI Pediatric Oct. 1 to Mar.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) Telemedicine encounters were completed using the following third-party vendors: Epic Warp (Epic Systems Corp, Verona, Wisconsin); Skype (Skype Communications, Palo Alto, California); FaceTime (Apple Inc, Cupertino, California); and Doximity (Doximity, San Francisco, California), depending on the patient preference. RAMETTA ET AL. (2020) Audio-video telemedicine SHENOY ET AL.…”
Section: Resultsmentioning
confidence: 99%
“…Most (86%) reported intending to pursue telehealth in future encounters. 25 An international survey of pediatric neurologists treating children with epilepsy revealed that about 25% of practitioners were seeing outpatients exclusively with telehealth and 95% were seeing at least some patients by telehealth. 26 A US-based single hospital system evaluation revealed that 67% of outpatient visits were completed via telehealth, 32% with phone visits, and only 1% of visits were in-person clinic encounters.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of telemedicine use in a child neurology clinic showed a high satisfaction rate among both patients and caregivers. Racial disparities in the delivery of remote health care were also identified, with minorities more likely to use telephone rather than video services (Rametta et al 2020). With time, iteration, and revision, telemedicine delivery will likely improve substantially and may, in fact, sustain even after restrictions have been lifted to replace in-person visits for those families who live remotely or are distanced from expert medical centres.…”
Section: Health Carementioning
confidence: 99%